Students’ Democratic Character and Problem-Solving Ability through Realistic Mathematics Education (RME) at Junior High School - Rezeki, Rike Arami; Johar, Rahmah; Usman, Usman (Jurnal Pendidikan Progresif, 2025)
Democratic Character and Problem Solving Ability Students through Realistic Mathematics Education (RME) at Junior High School. Students' democratic character and problem solving skills are still low. One of the efforts is by implementing the RME approach. This study aims to analyze students' democratic character, students' problem solving ability improvement, and problem solving ability in terms of students' democratic character after learning through the RME. This is the quantitative research with a one group pretest-posttest design. The population in this study was four classes of grade 8 students from one islamic junior high school/madrasah tsanawiyah (MTs) at Takengon, Aceh, Indonesia. The sample technique was simple random sampling. There were 45 students from two of four classes as a sample. The instruments in this study were observation sheets od students democratic character and problem solving test. Data analysis used an percentage of students’ character score, n-gain of students’ problem solving ability, and paired t-test to analyze the increasing of students’ problem solving ability. The results showed that the development of students' democratic character during the learning process through the RME approach was getting better; there was an increase in students' problem solving ability after participating in learning through the RME approach; and students with high and medium problem solving abilities have a good democratic character. The students' democratic character was further developed at the fourth meeting. Students were seen often to give opinions during group discussions, giving opportunities to express opinions for others, daring to respond to their friends' opinions, listening to their friends' opinions well, actively discussing, working on students’ worksheet together, and deliberating to draw conclusions together. Students’ democratic character can be trained through RME which has an impact on increasing their problem-solving ability. Keywords: democratic character, problem solving ability, realistic mathematics education (RME).